Testing the mediating role of perceived organizational support between leadership styles, organizational justice and employees' behavioral outcomes - Saad Hassan; Masood Ul Hassan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The current study was conducted to investigate the impact of Leader Member Exchange (LMX), Organizational Justice (OJ) and Empowering Leadership (EL) on Job Performance (JP), Organizational Citizenship Behavior (OCB) and Reduced Withdrawal Behavior (RWB) of employees working in the manufacturing sector of Pakistan. On the basis of theoretical support which provides the linkage between these variables, conceptual model and hypotheses were drawn. The data was collected through the adopted survey instrument, from the sample of 358 employees representing the manufacturing sector of Pakistan. Statistical software SPSS version 17 was used for factor analysis, correlation and regression analysis. The positive and significant results showed that EL, OJ and LMX impact on the Behavioral Outcomes of Employees directly and indirectly through the mediation of Perceived Organizational Support (POS). Finally, managerial & theoretical implications along with limitations and future recommendations have also been discussed in this study.
Keywords: 330; leader member exchange; organizational justice; empowering leadership; perceived organizational support; organizational citizenship behavior; job performance; reduced withdrawal behavior